People of the West - Duncan, Dayton; Ives, Stephen; Burns, Ken (Boston : Little, Brown and Company, 1996)
Tells the stories of fifteen men and women whose individual experiences provide a representative picture of life during the formative years of the American West.
"Based on the public television series The West."
Includes bibliographical references and index.
Keywords: Frontier and pioneer life; West (U.S.) -- History -- Juvenile literature; West (U.S.) -- Biography -- Juvenile literature; West (U.S.) -- Biography